2017
DOI: 10.1523/jneurosci.3070-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Ligase RNF138 Promotes Episodic Ataxia Type 2-Associated Aberrant Degradation of Human Cav2.1 (P/Q-Type) Calcium Channels

Abstract: Voltage-gated CaV2.1 channels comprise a pore-forming α1Asubunit with auxiliary α2δ and β subunits. CaV2.1 channels play an essential role in regulating synaptic signaling. Mutations in the human gene encoding the CaV2.1 subunit are associated with the cerebellar disease episodic ataxia type 2 (EA2). Several EA2-causing mutants exhibit impaired protein stability and exert dominant-negative suppression of CaV2.1 wild-type (WT) protein expression via aberrant proteasomal degradation. Here, we set out to delineat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…The levels of AnkB and Cav2.1 were enriched in control and AnkB glut+/− synaptosome fractions at P14 and P30, confirming localization to synaptic compartments (Fig. 6c) [18, 3941]. AnkB levels were lower in AnkB glut+/− synaptosomes than control synaptosomes, whereas Cav2.1 levels were unchanged, suggesting that the Cav2.1 synaptic pool remained unaffected.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The levels of AnkB and Cav2.1 were enriched in control and AnkB glut+/− synaptosome fractions at P14 and P30, confirming localization to synaptic compartments (Fig. 6c) [18, 3941]. AnkB levels were lower in AnkB glut+/− synaptosomes than control synaptosomes, whereas Cav2.1 levels were unchanged, suggesting that the Cav2.1 synaptic pool remained unaffected.…”
Section: Resultssupporting
confidence: 52%
“…AnkB interacts with Cav2.1, the pore-forming subunit of P/Q type VGCCs, in brain tissues isolated from adult mice [17]. Cav2.1 is detected pre- and post- synaptically, with multiple isoforms (ranging from 160 to 230 kDa, including a 190 kDa dominant isoform) expressed in brain [18, 19]. Cav2.1 plays a role in calcium-triggered neurotransmitter release at the presynaptic membrane, where it interacts with vesicle fusion machinery proteins, such as syntaxin 1A [2022].…”
Section: Introductionmentioning
confidence: 99%
“… 8 Higher expression of CAV2 has been associated with different types of cancer progression including lung, prostate, renal and breast cancer. 9 12 In breast tumor, CAV2 expression has been strongly associated with high histological grade 13 and poor prognosis. 14 Conflicting observations have been reported by Sagara et al, who found that CAV2 expression was suppressed in breast cancer tissues compared to normal tissues and that the reduced CAV1 was significantly associated with increasing tumor size.…”
Section: Introductionmentioning
confidence: 99%
“…However, of all E3 enzymes described only two, RFP2 and RFN138, have been found to associate with the pore-forming α 1 subunits of Ca V channels. The first one has been linked to the L-type Ca V 1.2 channels while the second to the P/Q-type Ca V 2.1 channels [ 8 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies indicate that the number of channels may be regulated by ubiquitination and proteasomal degradation, and also show that this process is carried out by specific enzymes of the Ubiquitin Proteasome System (UPS), as is the case of the E3 enzyme RFP2 that promotes the degradation of the Ca V 1.2 channels through an endoplasmic reticulum-associated mechanism known as ERAD [ 8 ]. It is also known that the UPS enzyme RNF14 is present in the microenvironment of the Ca V 2 channels and may regulate its activity [ 13 ], as well as the E3 ubiquitin ligase RNF138 that in conjunction with the auxiliary Ca V α 2 δ and β subunits dynamically regulates the Ca V 2.1α 1 subunit functional expression [ 14 ]. Also, we have recently shown evidence for the regulation of the Ca V 2.2 channels heterologously expressed in HEK-293 cells by the light chain 1 (LC1) of the microtubule-associated protein 1B (MAP1B), via increased ubiquitination of the channels [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%